Sensory Marketing Strategies to Enhance Elderly Customer Satisfaction: A Study at Kunokini Café & Resto - Adelia Rizma Yuniar; Lia Nirawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
As the global ageing population grows, the food and beverage (F&B) industry faces the challenge of catering to the evolving sensory needs of elderly customers, whose physical and sensory capacities gradually decline. This study investigates how sensory marketing practices shape the dining experience at KUNOKINI Café & Resto, emphasizing the need for tailored sensory elements to enhance comfort and satisfaction. This research uses a qualitative descriptive approach. Data were gathered through in-depth interviews with key informants, including elderly patrons, management, and staff, and observations of sensory elements such as lighting, music, aroma, and food texture. Findings indicate that while elements like ambient lighting, curated music, and food presentation are well-executed, specific needs of elderly customers remain unmet. They prefer non-glare lighting for visual clarity, soft-textured meals for easier consumption, low-volume music for a relaxed atmosphere, and spacious seating for enhanced physical comfort. Optimizing these elements can foster more inclusive dining experiences, strengthen customer engagement, and offer businesses a competitive edge.